(untitled) (Acta Scientiarum. Biological Sciences, 2011)
The effect of 2-pyridinecarboxylic acid (picolinic acid) on trypanosomes of the subgenus Schizotrypanum isolated from the bat Phyllostomus hastatus was determined in this study. Picolinic acid, at 50 µg mL-1, inhibited epimastigote growth by 99% after 12 days incubation. In addition, trypomastigote motility decreased by 50% after 6h and completely after 24h in the presence of 50 µg mL-1 picolinic acid. The 50% cytotoxic concentration on HEp-2 cell line was 275 µg mL-1 after 4 days incubation. Altogether, these results indicate higher toxicity against trypanosomes. The inhibitory effect of picolinic acid on epimastigote growth can be partially reversed by nicotinic acid and L-tryptophan, suggesting a competitive inhibition. Furthermore, two anti-Trypanosoma (Schizotrypanum) cruzi drugs were also evaluated with regard to bat trypanosome growth. Benznidazole, at 50 µg mL-1, inhibited epimastigote growth by 90% after 12 days incubation. Nifurtimox, at the same concentration, caused 96% growth inhibition after four days incubation. Corroborating a previous study, bat trypanosomes are a good model for screening new trypanocidal compounds. Moreover, they can be used to study many biological processes common to human pathogenic trypanosomatids.